Strategies for Enhancing Information and Communication Technology (ICT) Competence in Responding to the Demand for Technology-Literate Teachers - Muhammad Sayyed Ja’far Bolkia; Ahmad Baihaqi; Tamrin Tamrin; Apriliantoni Apriliantoni (Civiliza Publishing, Indonesia., 2026)
The rapid expansion of digital technology in the twenty-first century has repositioned Information and Communication Technology (ICT) competence as a core professional requirement for teachers rather than a supplementary skill. In the Indonesian context, the shift toward the Merdeka Curriculum, blended learning, and digital-based assessment has exposed a persistent gap between policy expectations and the actual technological readiness of educators, particularly in madrasah and Islamic higher education environments where infrastructural and pedagogical constraints remain considerable. This urgency is compounded by findings indicating that a substantial proportion of teachers are still not fully prepared to adapt to digital literacy demands, despite continuous government-led training initiatives. This article aims to examine the strategic dimensions through which ICT competence can be systematically improved among teachers, and to analyze how such strategies respond to the growing expectation that educators become technologically literate professionals. The study employs a qualitative library research (studi pustaka) design, drawing on peer-reviewed journal articles, institutional reports, and policy documents published within the last seven years, analyzed through content and thematic analysis techniques. The findings reveal that effective ICT competence enhancement rests on three interrelated strategies: structured and sustainable professional development programs, the integration of Technological Pedagogical Content Knowledge (TPACK) into everyday pedagogical practice, and institutional policy support accompanied by adequate digital infrastructure. The study concludes that technology-literate teachers emerge not merely from individual initiative but from a systemic convergence of training, pedagogical reorientation, and institutional facilitation. These findings contribute to the theoretical discourse on teacher digital competence and offer practical implications for Islamic education institutions seeking to accelerate their digital transformation agenda